Weakness Of Political Law Notice Not Reflecting Justice For Notary - Rais Firdaus Handoko (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2020)
The purpose of this paper is to show the role and authority of the Notary Public profession as a non-ASN official, and the need for a change in notary law politics in the form of changes to the formation of Notary regulations in the future so as to better guarantee justice and welfare for the Notaries. This study uses a normative juridical type of research with the specification of the study conducted analytically descriptive. Normative research uses secondary data types, namely data obtained from library studies. Data collection methods used by conducting Library Research (literature study) and techniques used in deciphering and processing the data collected is a qualitative description.Weaknesses of Notary regulations, both in the Civil Code and statutory regulations, are said by State officials but in practice the Notary independently looks for his own clients, so that it is more appropriate to say a general profession than State officials because they do not receive salary from the State and the role of the Notary from time to time is not doubt. Thanks to the performance of the Notary, economic traffic is particularly related to agreements, commitments, inheritance, etc., legal actions by the people who need and carry out legal actions helped in proving authentic deeds, so that they get legal certainty.This writing concludes that the Notary Public is a public official who is not an ASN official and needs further study by the government in the future in revising the Notary regulations. Also his advice on notary legal politics needs to be changed and the government of the relevant institutions authorized to form legislation should involve senior Notaries in revising Notary regulations.Keywords: Political Law; Notary; Justice.